Socialization of Registration Information for the Use of E-Book (ADKUH Book) at Puskesmas Colomadu 2 - Herawati Prianggi; Kresno Ario (Universitas Ibn Khaldun Bogor, 2023)
Background: Along with the development of technology and communication that is increasingly sophisticated and rapid, the flow of unlimited information is increasingly accessible, making technology a necessity for humans in carrying out all daily activities. This is also accompanied by the changing times that are increasingly rapid and limitless, bringing world civilization to the era of the fourth revolution. In this era, all activities are carried out by utilizing the existence of a technology, that prioritizes the process of automation and direct data exchange in the form of connectivity between humans, machines, and data covered in the Internet of Things and Artificial Intelligence with a combination of robotic technology and sensors by utilizing the existence of the internet as a link. Information and communication technology is the backbone of this fourth revolution movement, Objectives: The general purpose of this community service activity is to increase knowledge about access to health information and registration status at Colomadu 2 Health Center. Method: This method of community service activities uses socialization methods, tutorial questions and answers, and evaluation. Results: showed that the average knowledge score after ebook registration application education was dukuh (Mean= 15.29; SD= 2.64) is greater than the average knowledge score before education (Mean= 11.10; SD= 3.02), and this result is statistically significant (p<0.001).